Optimal Sizing of DGs in AC Distribution Networks via Black Hole Optimization (2018)
This paper presents a metaheuristic optimization technique named back hole optimization (BHO) for solving the problem of optimal dimensioning of distributed generation in radial distribution networks. This problem is formulated as a conventional optimal power flow problem in ac power grids. A master-slave methodology is proposed to solve this optimization problem. In the master stage the BHO technique decides the power output of each distributed generator (DG), while slave stage is responsible for solving the resulting power flow problem via classical sweep backward/forward technique. As comparison methods, classical particle swarm optimization as well as interior point methods are used. Two classical test systems with radial topologiesy and 33 and 69 nodes are used for numerical validations by using the MATLAB programming environment. Simulation results show the quality of the proposed optimization technique for power losses reduction in comparison with large-scale used optimization approaches available in specialized literature. © 2018 IEEE.